2010
DOI: 10.1002/ajmg.a.33514
|View full text |Cite
|
Sign up to set email alerts
|

Macrocephaly–capillary malformation: Analysis of 13 patients and review of the diagnostic criteria

Abstract: Macrocephaly-capillary malformation (M-CM) is a genetic syndrome of unknown etiology characterized by an enlarged head circumference and patchy, reticular capillary malformation. We describe the clinical features of 13 cases, report on the genome-wide Copy Number Variation characterization of these patients, analyze the main clinical features of this syndrome and propose a modification of the current diagnostic criteria: the inclusion of both overgrowth/asymmetry and neuroimaging alterations as major criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 26 publications
7
56
0
1
Order By: Relevance
“…More than 140 cases have been reported in the literature and numerous sets of diagnostic criteria proposed [Clayton-Smith et al, 1997;Moore et al, 1997;Franceschini et al, 2000;Lapunzina et al, 2004;Conway et al, 2007;Gonzalez et al, 2009;Martínez-Glez et al, 2010]. The most consistent features of MCAP appear to be congenital or early postnatal MEG and cutaneous capillary malformations, such as persistent nevus flammeus and/or vivid cutis marmorata .…”
Section: Mcap: a Disorder Of Brain And Body Overgrowthmentioning
confidence: 99%
“…More than 140 cases have been reported in the literature and numerous sets of diagnostic criteria proposed [Clayton-Smith et al, 1997;Moore et al, 1997;Franceschini et al, 2000;Lapunzina et al, 2004;Conway et al, 2007;Gonzalez et al, 2009;Martínez-Glez et al, 2010]. The most consistent features of MCAP appear to be congenital or early postnatal MEG and cutaneous capillary malformations, such as persistent nevus flammeus and/or vivid cutis marmorata .…”
Section: Mcap: a Disorder Of Brain And Body Overgrowthmentioning
confidence: 99%
“…It is presumed to be genetic in origin; however, no common genetic defect has yet been found, 9 although a subset of these patients may have PIK3CA mutations. 11 It appears likely that many of these patients are genetic mosaics, with abnormalities manifesting in the tissues that carry a mutation.…”
Section: Discussionmentioning
confidence: 99%
“…There are several characteristic imaging findings in MCAP, including ventriculomegaly, cavum septum pellucidum, cerebellar tonsillar herniation, and cerebral and/ or cerebellar asymmetry. 9 Several diagnostic criteria schemata have been proposed 3,4,6,9,12,15 based on anatomical and radiographic findings, but there is no clear diagnostic consensus yet. Diagnosis is made based on clinical criteria alone.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Imaging studies are indicated only for the evaluation of suspected congenital anomalies. 49,51 In 2009 some Authors proposed diagnostic criteria for CMTG based on the presence of all three major criteria and at least two or more minor criteria. (Table 2) However, the diagnostic validity of these criteria has not been confirmed yet and further studies are needed for this purpose.…”
Section: Discussionmentioning
confidence: 99%